La estimulación sensorial en el inicio de la lectura de niños de primer año de educación básica de la Unidad Educativa “San Vicente de Paúl”, cantón Riobamba período académico noviembre – abril del 2020-2021 - Herrera López, Michelle Alejandra (2021)
This research called "sensory stimulation at the beginning of the reading of children in the first year of elementary education of the educational unit San Vicente de Paul", Riobamba canton, in the academic period November 2020- April 2021, aimed to analyze the variants corresponding to Sensory Stimulation and at the beginning of reading determined in the TALE test in the process of initiation to reading in first-year boys and girls. A qualitative research design was employed; in turn, it allowed to collect information and analyze a criterial contribution. The obtained results from a population of 30 children determine positive and negative responses; this is beneficial for the learning of each of the children through the applied methodologies, (Games, pictograms, stories, etc.) The techniques applied for this research were of great benefit to each student. It was observed that the most beneficial methodology was the realization of pictograms for reading. The utilized tactic is attestable by the classroom tutor concerning the obtained knowledge with the children. It can be determined that children need to have good sensory stimulation to achieve better learning, increase motor and cognitive capacity and thus have a better performance in their reading process.